THE COMPETITIVENESS OF INDONESIAN TUNA EXPORT FACING THE ASEAN ECONOMIC COMMUNITY - Apridar . (Aceh International Journal of Social Science, 2014)
Abstract: This study tried to estimate the competitiveness of Indonesian tuna exports in the ASEAN market during the period 2005-2010 and analyze the factors affecting the competitiveness of exports of tuna. Several data analysis methods were used to measure the commodity of Indonesian tuna with competitiveness to the ASEAN market are the Revealed Comparative Advantage (RCA) and Constant Market Share Analysis (CMSA); while the panel data regression is used to examine the factors that affect the export competitiveness of Indonesian tuna to the ASEAN countries. This is indicated by the value of RCA obtained less than 1. This also shows that the competitiveness of Indonesian tuna is still relatively high (strong); while the value of CMSA is positive, it indicates that Indonesia is still be able to maintain the competitiveness of tuna fish in the ASEAN market. RCA and CMSA size is then used as the dependent variable in the regression analysis panel. The results of the panel regression estimated using a random effects indicate that GDPi negative and significant, while GDPj, POPj, Distance and exports have a positive and significant effect on RCA. The result of the pooled least square estimation indicates that GDPi and POPi are negative and significant, while the POPj gives a positive and significant influence toward CMSA decreased. Keywords: Competitiveness Revealed Comparative Advantage, Constant Market Share Analysis, Panel Data Regression